PENGARUH KEBIJAKAN DIVIDEN DAN DAN PERTUMBUHAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DI BEI - Yuniarti, Rina (JURNAL EKOMBIS REVIEW, 2014)
Rina Yuniarti; This study aimed to determine the effect of dividend policy, the company's growth to firms value. The populationin this study is the manufacturing company listed of the Indonesia Stock Exchange (BEI) in the year from 2006 to 2010.The hipotesis of this study were tested by exploring multiple regresi and technical regression nalysis SPSS 18. This study faund that dividen policy and company?s growth positive infemence firm value. Key words: dividend policy, the company?s growth and firm value